Systematic Performance Analysis in Foreign Language Instruction - Prokop, Manfred ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
This paper reports on the development of an error-coding instrument and a computerized continuous feedback system for the diagnostic evaluation and remedial treatment of unstructured second-language performances and the use of such a system in an instructional setting. The system does the following: it allows quick, objective, accurate, and detailed evaluation of "creative" written and spoken German; it provides student performance files in the structural and phonological elements of the language that can be updated as required; it allows accurate performance-to-performance comparisons of progress; it permits the instructor to determine quickly the learning status of an individual student, a group of students, or the entire class, and subsequently to design appropriate exercises for that particular target group; and it allows students to judge their performance from the same criteria which were available to their instructor for marking. Feedback procedures and a tabulation of errors for three levels of German language instruction are presented and their systemic implications for the design of pedagogical grammars are discussed. (Author/KM)
ERIC Note: Paper prepared for the World Congress of AILA, the International Association of Applied Linguistics (4th, Stuttgart, August 1975).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Computer Assisted Instruction; Diagnostic Teaching; Educational Diagnosis; Error Analysis (Language); Error Patterns; Evaluation Methods; German; Individualized Instruction; Language Instruction; Language Learning Levels; Linguistic Performance; Models; Second Language Learning; Student Evaluation; Verbal Communication; Reports, Research